2008
DOI: 10.1080/10615800701849902
|View full text |Cite
|
Sign up to set email alerts
|

Test anxiety in Indian children: A cross-cultural perspective

Abstract: The present investigation examined test anxiety in Indian children from a cross-cultural perspective. Test anxiety has been studied extensively in western countries but much less so in eastern countries. Furthermore, the cross-cultural research conducted in eastern countries possesses significant limitations and continues to possess a western bias. The present research attempted to advance cross-cultural research on test anxiety by adopting Berry's imposed etic-emic-derived etic methodology. Participants inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
0
17
1
2
Order By: Relevance
“…It is possible that future norming studies will identify gender-based norms, age-based norms, or cultural standards. For example, empirical investigations have demonstrated that students from Islamic and Eastern cultures often report significantly higher levels of test anxiety than their Western counterparts (Bodas, Ollendick, & Sovani, 2008; Sharma & Sud, 1990). Previous examinations have noted socialization practices, parental expectations, and the sociocultural framework of the educational settings may contribute to the disparate pattern of test anxiety observed during cross-cultural examinations (Bodas & Ollendick, 2005; Bodas et al, 2008; Furlan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that future norming studies will identify gender-based norms, age-based norms, or cultural standards. For example, empirical investigations have demonstrated that students from Islamic and Eastern cultures often report significantly higher levels of test anxiety than their Western counterparts (Bodas, Ollendick, & Sovani, 2008; Sharma & Sud, 1990). Previous examinations have noted socialization practices, parental expectations, and the sociocultural framework of the educational settings may contribute to the disparate pattern of test anxiety observed during cross-cultural examinations (Bodas & Ollendick, 2005; Bodas et al, 2008; Furlan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using samples from different countries provide evidence that females tend to report higher levels of overall test anxiety than do males (Lowe and Lee 2008;Putwain, 2007;Segool, Carlson, Goforth, von der Embse, and Barterian, 2010). This effect is frequently attributed to socialization practices that encourage females to display their emotions/feelings more openly whereas pushing males to exhibit defensiveness about admitting their emotions/feelings (Bodas et al, 2008); and also to parental expectations that force females to achieve better and thus trigger females' sensitivity about getting social approval from adults than do males (Wigfield and Eccles, 1989).…”
Section: Gender Differencesmentioning
confidence: 99%
“…Testing is a common occurrence in schools in the United States and abroad (Bodas & Ollendick, 2005;Bodas, Ollendick, & Sovani, 2008;Lowe et al, 2008). Students' test scores are used to evaluate the quality of schools, to assist in educational decision making, and to determine whether students are meeting educational expectations (Every Student Succeeds Act, 2015;Jacob, Decker, & Timmerman Lugg, 2016).…”
Section: Introductionmentioning
confidence: 99%